Synergistic effects of novel herbal decoctions from Panax ginseng and Morus alba on tyrosinase activity and melanogenesis in vitro. Issue 2 (February 2022) - Kim, Ji Hye; Kim, Tae In; Ma, Jin-Yeul
Abstract: Many medicinal plants such as a Panax ginseng and Morus alba (mulberry tree) have been widely used as depigmenting agents in Asia. To maximize their synergistic effects on melanogenesis, new herbal decoctions were created by mixing Ginseng Radix Alba (GR) and Mori Radicis Cortex (MC) at a ratio of 3:2 which called GMC decoction. A decoction of GR and Mori Ramulus (MR), which called GMR, was also formulated in order to compare the anti-melanogenic capacity. Combined decoctions, GMC and GMR, significantly decreased mushroom tyrosinase activity in vitro ; however, single extracts, including MC and MR, showed weaker inhibitory activity. Melanin content assay and Fontana–Masson staining confirmed that two decoctions showed stronger inhibitory effects on the forskolin-induced melanin level in B16 cells, without cytotoxicity. Our findings suggest that ginseng in combination with mulberry tree enhances the anti-melanogenic effect in vitro . Abstract : Herbal decoction, Ginseng Radix Alba extract, Mori Radicis Cortex extract, Mori Ramulus extract, Tyrosinase, Melanin.